Four square method for improving students’ writing ability in EF Teens & Kids Kalimalang - Lumenta, Febriany Maria; Surista, Ade; Kurnia, Ahmad (CV. Mitra Palupi, 2020)
Background: Children are easily to speak up their idea directly but do not know how to shift it into proper writing. The children, English learners, need the writing aspect due to fulfill every English aspect especially in their school academicPurpose: This research is going to increase the students’ writing ability through eclectic method.Design and methods: This research has another concept with drawing the eclectic method in different ways. The writer tries to put four square writing methods in order to apply the eclectic method in developing students’ writing ability in EF Kids and Teens Kalimalang. This research is a descriptive quantitative research which will be done by field work. In this research, the writer uses the descriptive and quantitative design to analyze the data. The instrument and variable of this research consist of several parts. They are the directive of teaching method, the directive of the test form, and the result test.Results: The combining of Four Square Writing Method and classroom writing performance as Eclectic Method significantly improves the students’ score. It is clearly showed by the increasing of the mean score. The mean score of the pretest is 68.46% while the mean score of the posttest is 79.13% which increased 10.46%.